Integrasi Teknologi Artificial Intellegence (AI) Dalam Pembelajaran PAI - Ulumuddin, Ihya (ILJ: Islamic Learning Journal, 2025)
The development of digital technology, particularly Artificial Intelligence (AI), has had a significant impact on education, including Islamic Religious Education (IRE). This study aims to describe the concept of AI integration in IRE, analyze its opportunities and benefits, identify challenges, and formulate implementation strategies that are in line with Islamic values. The research method used a descriptive qualitative approach with a literature study of relevant articles, books, and proceedings from 2020 to 2025. The results show that AI has the potential to increase interactivity, effectiveness, and personalization in PAI learning, as well as ease teachers' administrative tasks. However, there are challenges in the form of infrastructure limitations, low digital literacy among teachers, and ethical and privacy issues. The conclusion of the study emphasizes that AI is only instrumental and cannot replace the role of teachers as moral and spiritual role models. The integration of AI in PAI can be successful if it is done in a balanced manner, with the support of teacher training, adaptive curricula, and strict supervision of technology-based Islamic content.